Extending the southern range of four shrimps (Crustacea: Decapoda: Stenopodidae, Hippolytidae and Alpheidae) in southwestern Atlantic (27o S) and confirming the presence of Mediterranean Stenopus spinosus Risso, 1827 in Brazil - Giraldes, Bruno Welter; Freire, Andrea Santarosa (Zootaxa, 2015)
In subtidal zones, certain shrimp species with cryptic behaviour represent a gap in the biodiversity description in many places in the world. This study extends the southern limit of Stenopus hispidus (Oliver, 1811), Alpheus formosus Gibbes, 1850, Alpheus cf. packardii Kingsley, 1880 and Lysmata ankeri Rhyne & Lin, 2006 to Santa Catarina State—Brazil, 27oS. The results also confirm the new occurrence of Stenopus spinosus Risso, 1827 in Brazilian waters. All specimens were collected by scuba diving from rocky islands between 3 and 25 meters depth. We present for each species certain taxonomic features in colour images that will help to identify these decapods in situ in further monitoring programs.